Flag Manifolds for the Characterization of Geometric Structure in Large Data Sets - Marrinan, Tim; Beveridge, J. Ross; Draper, Bruce; Kirby, Michael; Peterson, Chris (Numerical Mathematics and Advanced Applications-ENUMATH 2013)

Asymptotic parameter tracking performance with measurement data of 1-bit resolution - Stein, Manuel; Kürzl, Alexander; Mezghani, Amine; Nossek, Josef A. (IEEE Trans.\ Signal\ Process.)

Experimental evaluation of interference alignment for broadband WLAN systems - Lameiro, Christian; García-Naya, Jose A.; Santamaría, Ignacio; Castedo, Luis (EURASIP Journal on Wireless Communications and Networking)

Performance Analysis of Volume-based Spectrum Sensing for Cognitive Radio - Huang, L.; Qian, C.; Xiao, Y-.H.; Zhang, Q. T. (IEEE Transactions on Wireless Communications)

Robust Spectrum Sensing for Noncircular Signal in Multiantenna Cognitive Receivers - Huang, L.; Xiao, Y-.H.; Zhang, Q. T. (IEEE Transactions on Signal Processing)

A simple DoF-achievable scheme for the Gaussian interference channel with delayed CSIT - Rezaee, M.; Schreier, P. J.; Guillaud, M.; Clerckx, B. (Proc. IEEE Global Communications Convference: Communication Theory)

Signal parameter estimation performance under a sampling rate constraint - Lenz, Andreas; Stein, Manuel; Nossek, Josef A. (Asilomar Conf.\ Signals Syst.\ Computers)

An asymptotic LMPI test for cyclostationarity detection with application to Cognitive Radio (invited paper) - Ramírez, D.; Schreier, P. J.; Vía, J.; Santamaría, I.; Scharf, L. L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We propose a new detector of primary users in cognitive radio networks. The main novelty of the proposed detector in comparison to most known detectors is that it is based on sound statistical principles for detecting cyclostationary signals. In particular, the proposed detector is (asymptotically) the locally most powerful invariant test, i.e. the best invariant detector for low signal-to-noise ratios. The derivation is based on two main ideas: the relationship between a scalar-valued cyclostationary signal and a vector-valued wide-sense stationary signal, and Wijsman’s theorem. Moreover, using the spectral representation for the cyclostationary time series, the detector has an insightful interpretation, and implementation, as the broadband coherence between frequencies that are separated by multiples of the cycle frequency. Finally, simulations confirm that the proposed detector performs better than previous approaches.

An Experimental Evaluation of Broadband Spatial IA for uncoordinated MIMO-OFDM Systems - Fanjul, Jacobo; Lameiro, Christian; Santamaría, Ignacio; García-Naya, Jose A.; Castedo, Luis (Proc. IEEE Int. Conf. Digital Signal Process.)
In this paper we present an experimental study on the performance of spatial Interference Alignment (IA) in broadband indoor wireless local area network scenarios that use Orthogonal Frequency Division Multiplexing (OFDM) according to the IEEE 802.11a physical-layer specifications. Experiments have been carried out using a wireless network testbed made up of six nodes equipped with Multiple-Input Multiple-Output (MIMO) radio interfaces. This setup allows the implementation of a 3-user MIMO interference channel. We have implemented different IA decoding schemes that operate either before or after the Fast Fourier Transform block. IA has been experimentally evaluated comparing both approaches to analyze its performance in synchronous and asynchronous transmissions. Our results indicate that spatial IA performs satisfactorily in practical broadband indoor scenarios in which wireless channels often exhibit relatively large coherence times.

Ranging with high accuracy and without ambiguities - Theiler, Sebastian; Stein, Manuel; Nossek, Josef A. (Proc.\ IEEE Work. Pos.\ Nav. & Com.)